Structural diversity of neuronal calcium sensor proteins and insights for activation of retinal guanylyl cyclase by GCAP1 - Lim, Sunghyuk; Dizhoor, Alexander; Ames, James (Frontiers in Molecular Neuroscience, 2014)
Neuronal calcium sensor (NCS) proteins, a sub-branch of the calmodulin superfamily, are expressed in the brain and retina where they transduce calcium signals and are genetically linked to degenerative diseases. The amino acid sequences of NCS proteins are highly conserved but their physiological functions are quite different. Retinal recoverin controls Ca2+-dependent inactivation of light-excited rhodopsin during phototransduction, guanylyl cyclase activating proteins 1 and 2 (GCAP1 and GCAP2) promote Ca2+-dependent activation of retinal guanylyl cyclases, and neuronal frequenin (NCS-1) modulates synaptic activity and neuronal secretion. Here we review the molecular structures of myristoylated forms of NCS-1, recoverin, and GCAP1 that all look very different, suggesting that the attached myristoyl group helps to refold these highly homologous proteins into different three-dimensional folds. Ca2+-binding to both recoverin and NCS-1 cause large protein conformational changes that ejects the covalently attached myristoyl group into the solvent exterior and promotes membrane targeting (Ca2+-myristoyl switch). The GCAP proteins undergo much smaller Ca2+-induced conformational changes and do not possess a Ca2+-myristoyl switch. Recent structures of GCAP1 in both its activator and Ca2+-bound inhibitory states will be discussed to understand structural determinants that control their Ca2+-dependent activation of retinal guanylyl cyclases.